PERENCANAAN PENGGUNAAN TANAMAN HIAS UNTUK FITOREMEDIASI RUANGAN DALAM (INDOOR) APARTEMEN DARI PAJANAN PARTIKULAT - Elfira Aprilia; Bieby Voijant Tangahu (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2022)
Indoor air pollution is a condition of the presence of pollutants whose concentrations can risk causing human health problems. One type of air pollutant that has an impact on health is particulate matter (PM) because it is respirable which triggers respiratory problems. There are several factors that cause the effect of indoor particulate concentrations by apartment residents, which is outdoor factors such as the influence of transportation activities. Phytoremediation is one of the solutions to reduce excess particulates. So that the objectives to be achieved from this planning are to identify particulate exposure in the apartment room, inventory ornamental plants that are suitable in indoor air phytoremediation, and plan the needs of ornamental plants. Particulate concentration measurements were carried out in the apartment room at 3 predetermined unit locations. The selection of apartment rooms by considering the distance from the room to the parking lot as a comparison. After measuring particulate matter, 3 out of 3 units for measuring PM2.5 concentration showed results above the quality standard according to the Minister of Health Regulation No. 1077 of 2011. As for the PM10 measurement, only 1 out of 3 units showed results above the quality standard. Because it has several advantages, to reduce the concentration of particulates in the room, the phytoremediation method using ornamental plants is used. Phytoremediation itself is a method to clean or control contaminants using plants. The need for indoor ornamental plants is planned by considering the level of plants reduction so that the particulate concentration does not exceed the quality standard and is calculated using the approach method. In units A and B, 3 ornamental plants are planned, while unit C only requires 2 ornamental plants to reduce PM2.5 and PM10.